Aircraft cabin lighting design method based on DIALux - FU Jinchi; CHEN Dengkai; ZHANG Xian; XIE Ning (Xibei Gongye Daxue Xuebao, 2024)
Lighting in aircraft cabin is an important part of the aircraft interior lighting system. A reasonable cabin lighting design can improve the quality of flight services and enhance passenger satisfaction and comfort. In this paper, an aircraft cabin lighting design method is proposed based on the DIALux calculation and simulation software. Based on a quantitative evaluation, calibration and analysis of average illuminance, glare and uniformity of illuminance from the perspectives of travel safety, visual comfort and high quality service, the method explores and proposes an innovative approach to the design of aircraft cabin lighting. Finally, based on this method, an optical simulation model is established and visual simulation calculations are carried out to verify the feasibility of the method.